2023
DOI: 10.3389/fnut.2023.1092544
|View full text |Cite
|
Sign up to set email alerts
|

Myo-inositol supplementation improves cardiometabolic factors, anthropometric measures, and liver function in obese patients with non-alcoholic fatty liver disease

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) as the hepatic manifestation of metabolic syndrome is closely associated with type 2 diabetes mellitus. Myo-inositol (MI)—a 6-C sugar alcohol—with insulin-mimetic, anti-diabetic, lipid-lowering, and anti-inflammatory properties has exerted favorable effects on insulin resistance-related disorders and metabolic disease, while recent animal studies revealed its positive effects on liver function. This study aimed to investigate the effects of MI supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Table 5 demonstrates changes in serum liver enzymes. As we reported in our previously published paper (Arefhosseini et al., 2023 ), serum levels of ALT and AST decreased significantly in both groups. At the end of the study, MI supplementation for 8 weeks only showed improvements in the AST/ALT ratio but not in serum AST, after adjusting for the confounders.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Table 5 demonstrates changes in serum liver enzymes. As we reported in our previously published paper (Arefhosseini et al., 2023 ), serum levels of ALT and AST decreased significantly in both groups. At the end of the study, MI supplementation for 8 weeks only showed improvements in the AST/ALT ratio but not in serum AST, after adjusting for the confounders.…”
Section: Resultssupporting
confidence: 87%
“…Table 5 demonstrates changes in serum liver enzymes. As we reported in our previously published paper (Arefhosseini et al, 2023), serum levels of ALT and AST decreased significantly in both groups.…”
Section: Liver Enzymessupporting
confidence: 88%
See 2 more Smart Citations
“…It is a growing health concern globally and has been associated with modern lifestyle habits such as a sedentary lifestyle, unhealthy diet, and excessive alcohol consumption [16]. The primary cause of fatty liver is the accumulation of fat in the liver cells.…”
Section: Introductionmentioning
confidence: 99%